The efficacy of managing fluid overload in chronic peritoneal dialysis patients by a structured nurse-led intervention protocol - Law, Man Ching (BMC Nephrol, 2019)
BACKGROUND: Extracellular volume overload is a common problem in peritoneal dialysis (PD) patients and is associated with excessive mortality. We determine the effectiveness of treating PD patients with extracellular volume overload by a structured nurse-led intervention program. METHODS: The hydration status of PD patients was screened by bioimpedance spectroscopy (BIS). Fluid overload was defined as overhydration volume ≥ 2 L. Patients were classified into Symptomatic and Asymptomatic Groups and were managed by a structured nurse-led intervention protocol that focused on education and motivation. Hypertonic cycles were given for short term symptom relief for the Symptomatic group. Patients were followed for 12 weeks for the change in volume status, blood pressure, knowledge and adherence as determined by standard questionnaires. RESULTS: We recruited 103 patients (53 Symptomatic, 50 Asymptomatic Group. There was a significant reduction in overhydration volume 4 weeks after intervention, which was sustained by week 12; the overall reduction in overhydration volume was 0.96 ± 1.43 L at 4 weeks, and 1.06 ± 1.70 L at 12 weeks (p < 0.001 for both). The improvement was significant for both Symptomatic and Asymptomatic Groups. There was a concomitant reduction in systolic blood pressure in the Asymptomatic (146.9 ± 20.7 to 136.9 ± 19.5 mmHg, p = 0.037) but not Symptomatic group. The scores of knowledge, adherence to dietary control and advices on daily habit at week 4 were all significantly increased, and the improvement was sustained at week 12. CONCLUSIONS: The structured nurse-led intervention protocol has a lasting benefit on the volume status of PD patients with extracellular volume overload. BIS screening allows prompt identification of volume overload in asymptomatic patients, and facilitates a focused effort on this high risk group.